ETHNIC OPPRESSION IN R.F. KUANG’S THE POPPY WAR BOOK - Kanza, Balqis Affanin; Thoyibi, M. (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
This study explores the representation of ethnic oppression in R.F. Kuang’s The Poppy War (2018) using a qualitative literary approach. It focuses on three main objectives: (1) identifying indicators of ethnic oppression within the novel; (2) analyzing how these forms of oppression are portrayed through literary elements such as characterization, setting, and plot; and (3) examining the motivations behind Kuang’s engagement with this theme. The primary data source is the novel itself, supported by secondary materials including academic journals, interviews, and historical texts. The analysis reveals three dominant indicators of ethnic oppression in the novel: systemic marginalization, cultural erasure, and institutional prejudice. These are conveyed through narrative elements and key events involving marginalized groups such as the Speerlies. The findings suggest that Kuang uses the fantasy setting of The Poppy War to reflect on historical injustices and process personal and familial trauma rooted in real-world events. Through this lens, the novel serves as both social critique and historical reflection.